Multifunctional TPU composite foams with embedded biomass-derived carbon networks for electromagnetic interference shielding. (February 2022) - Jia, Xichen; Shen, Bin; Chen, Jiali; Wang, Guoqing; Sun, Zhouping; Zheng, Wenge
Abstract: Although flexible and lightweight electromagnetic interference (EMI) shielding materials have drawn a host of interest in recent years, it is still an issue to design multifunctional polymer composite foams reinforced with biomass-derived 3D carbon skeletons for integrating outstanding performances in EMI shielding, thermal isolation and joule heating. Herein, lightweight and flexible thermoplastic polyurethane (TPU) composite foams with the combination of highly conductive cotton-derived 3D carbon networks and microporous elastic TPU skeleton have been manufactured by facile freeze-drying method, and they could not only show high shielding effectiveness up to ∼68 dB at low thickness and density (∼0.2 g/cm 3 ), but also possess satisfactory thermal-insulation performance and excellent low-voltage driven joule-heating capability with good recyclability and long-term durability. The multifunctionality of such foams could provide the ability to minimize the influence of external temperature on the working performance of protected electronic equipments during EMI shielding, suggesting the availability and effectiveness of biomass-derived 3D carbon skeletons for preparing flexible and multifunctional CPC foams. Graphical abstract: Image 1 Highlights: Flexible TCC foams with cotton-derived 3D carbon networks and microporous TPU skeleton are manufactured by facile freeze drying. TCC foams exhibit outstanding EMI-shielding performance with an eximious cycling durability. TCC foams possess satisfactory thermal-insulation performance and excellent low-voltage driven joule-heating capability.